Interferensi Morfologi Bahasa Aceh dalam Tulisan Bahasa Indonesia Mahasiswa Universitas Teuku Umar - Siti Jahria Sitompul; Agus Pratama; Al Zuhri; Nurasma Aripin (Pencerah, 2021)
Indonesian (BI) has the position and function as the national language and the official language of the state. This causes the need for Indonesian to be fostered and developed as a standard language. However, Indonesian language development according to official linguistic rules is often neglected due to language interference or deviation due to the influence of regional languages that are inherent in the Indonesian nation. This interference even occurs among students whose ideas and thoughts must go through scientific writing according to official linguistic rules. This clearly hinders the smooth communication that should not happen again to students. This study uses a qualitative approach with a description model that describes systematically, factually, and accurately about the data and characteristics of the phenomenon under study. The data collection technique used in this research is to use observation techniques with written data tools, namely through making essays with free themes. Based on the results of this study, the researchers found four morphological interferences of the Acehnese language to Indonesian from all Teuku Umar University students who settled or lived in alue bata. The four words consist of three basic words, namely: laot, tepong, and tawe and one reduplication word (repeat) namely meunasah-meunasah. This should be avoided so that the Indonesian language as the nation's identity is maintained according to the applicable rules, because these forms of interference can damage Indonesian as the official language of the state which should be protected and maintained according to the applicable rules.